B1-SINE retrotransposons: Establishing genomic insulatory networks - Román, Angel C (Landes Bioscience, 2011)
More than half the size of most mammalian genomes is composed by repetitive sequences. Short Interspersed Nuclear Element (SINE) retrotransposons constitute one of the main components of the genomic repetitive fraction. The abundance and evolutionary conservation of these sequences support their contribution to maintain the stability and proper function of the genome. Several recent studies have unveiled some of these intriguing tasks, which include, but are not limited to the control of transcriptional regulation and the organization of the chromatin. Here, we will comment on our recent report characterizing the insulator/boundary activity of a novel B1 SINE retrotransposon (B1-X35S) widely present in the mouse genome. A remarkable finding was that B1-X35S-dependent insulation required not only the combinatorial binding of transcription factors dioxin receptor (AhR) and Snai2/Slug, but also a molecular switch between RNA Polymerases (Pol) Pol III and Pol II. Moreover, B1-X35S seemingly forms heterochromatic barriers next to gene promoters that bioinformatic analyses revealed to dramatically change from embryonic stem (ES) to fibroblasts cells. The vast presence of B1-X35S in the mouse genome (over 14,000 instances) opens the exciting possibility of a complex network in which retrotransposon-derived insulators convert biological input signals into transcriptional responses by defining gene expression domains. The importance of such mechanism in different cellular and physiological processes will be discussed.